Shared selves : Latinx memoir and ethical alternatives to humanism - Bost, Suzanne (Transformations (University of Illinois (System). Press), 2019)
"Memoir typically places selfhood at the center. Interestingly, the genre's recent surge in popularity coincides with breakthroughs in scholarship focused on selfhood in a new way: as an always renewing, always emerging entity. Suzanne Bost draws on feminist and posthumanist ideas to explore how three contemporary memoirists decenter the self. Latinx writers John Rechy, Aurora Levins Morales, and Gloria E. Anzaldúa work in places where personal history intertwines with communities, environments, animals, plants, and spirits. This dedication to interconnectedness resonates with ideas in posthumanist theory while calling on Indigenous worldviews. As Bost argues, our view of life itself expands if we look at how such frameworks interact with queer theory, disability studies, ecological thinking, and other fields. These webs of relation in turn mediate experience, agency, and life itself"--